Miasmatic approach towards Obese Patients with Genetic Influence (Homoeopathy for All, 2023)
Obesity is a recognized medical disorder  characterized by the accumulation of  excessive body fat, resulting in various  health complications and a potential  decrease in life expectancy for those  affected.1 Obesity and overweight have  grown to be serious public health issues  in both developing and rich nations,  and they pose enormous difficulties for  maintaining the gains in world health.  The prevalence of overweight and  obesity has risen in developing nations  such as India due to demographic,  epidemiological, and nutritional  changes. These changes have resulted in  a decline in the burden of communicable  diseases and fertility rates, but non communicable diseases (NCDs) have  become more prevalent.2
Keywords: Miasmatic; approach; Patients